STUDY STREAM PLATFORM - A MODERN SOLUTION FOR ORGANIZING STUDENTS ’INDEPENDENT WORK - Orlova, Olena Ihorivna (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2021)
The article reveals the problems, methods and means of organizing self-studying activities of students, especially during the distance learning.The author provides recommendations for using the modern StudySream platform to maintain the level of self-study of students.